Raggedy Ann stories - Gruelle, Johnny (New York Avenel, N.J. Derrydale Books Distributed by Outlet Book Co., 1993)
Presents a collection of Raggedy Ann stories, including "Raggedy Ann Rescues Fido," and "Raggedy Ann and the Kittens."
69431
Keywords: Children's stories, American; Dolls -- Fiction